2008
DOI: 10.1021/cg800791s
|View full text |Cite
|
Sign up to set email alerts
|

Morphologically Controlled Fibrous Spherulites of an Apatite Precursor Biocrystal

Abstract: Unique and characteristically formed spherulitic crystals of octacalcium phosphate (OCP, Ca8H2(PO4)6·5H2O) were grown for the first time by the gel method, using the system Ca(NO3)2−(NH4)2HPO4−agar. The shape of test tubes crucially affected the morphological development of the OCP crystals. The feature of OCP spherulites grown in U-type test tubes was an aggregation of a relatively ordered, large number of ultralong and flexible whiskers radiating from the center region of the spheres, resulting in high poros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…This method is especially useful for crystal growth of poorly soluble compounds. Many sparingly soluble inorganic compounds, such as calcium carbonate [1][2][3][4], calcium phosphate [5][6][7][8][9][10][11][12], calcium tartrate [13,14], and calcium oxalate [15], have been synthesized in gels. The crystals formed in the gel can have a variety of morphologies: dominant factors affecting crystal morphology are degree of supersaturation, rate-determining step of crystal growth, and interactions between the gel molecules and crystals and/or ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is especially useful for crystal growth of poorly soluble compounds. Many sparingly soluble inorganic compounds, such as calcium carbonate [1][2][3][4], calcium phosphate [5][6][7][8][9][10][11][12], calcium tartrate [13,14], and calcium oxalate [15], have been synthesized in gels. The crystals formed in the gel can have a variety of morphologies: dominant factors affecting crystal morphology are degree of supersaturation, rate-determining step of crystal growth, and interactions between the gel molecules and crystals and/or ions.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium phosphate crystals have been synthesized in various kinds of organic hydrogels, and calcium phosphate-hydrogel composite materials are expected to be useful as bone-repairing materials. As a media for crystal growth, natural or synthetic organic hydrogels such as gelatin [7], agar [8], fibrin [9], polyacrylamide (PAAm) [10,11], and poly(acrylic acid) (PAA) [12] have been used in these fundamental studies of development of bone-repairing materials. Gelatin, fibrin, and agar are typical biodegradable natural polymers, and hence composites of calcium phosphate and these natural polymer hydrogels can be regard as biodegradable bone-repairing materials.…”
Section: Introductionmentioning
confidence: 99%
“…Morphosynthesis mediated by the dilute ion-dopants or organic additives is rapidly developed in Nanochemistry [9][10][11][12]. However, much attention is only paid to the effect of biomacromolecules and synthetic polymers on controlling polymorph, size, and superstructure expression of CaP crystals [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, TEM investigation of OCP whiskers was conducted by Teshima et al 22 , who reported that the elongated direction corresponds to the 0001 directions, and that the crysta l elongates predominantly in the 0001 directions, due to the (10 1 0) face being more stable than the (0001) or the (10 1 1) end faces. The same anisotropic crystal growth seems to be occurred by the optimized preparation conditions.…”
mentioning
confidence: 99%